2013
DOI: 10.1155/2013/579129
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Protection by Fabric Engineering

Abstract: Background. The increasing emission of greenhouse gases has evoked the human being to save the ozone layer and minimize the risk of ultraviolet radiation (UVR). Various fabric structures have been explored to achieve desired ultraviolet protection factor (UPF) in various situations. Objective. In this study, the effect of various filament configurations like twisted, flat, intermingled, and textured in multifilament yarns on fabric in different combinations is assessed in order to engineer a fabric of better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In fact, there are several textile products currently in the market that claim to have properties usually found in cosmetics [2], such as moisturizing, slimming, energizing, refreshing, relaxing or vitalizing properties, as well as UV protection [3][4] or simply fragrance. Thus, there is a real need to develop test methods to verify the effectiveness and durability of these claimed properties [5].…”
Section: /12mentioning
confidence: 99%
“…In fact, there are several textile products currently in the market that claim to have properties usually found in cosmetics [2], such as moisturizing, slimming, energizing, refreshing, relaxing or vitalizing properties, as well as UV protection [3][4] or simply fragrance. Thus, there is a real need to develop test methods to verify the effectiveness and durability of these claimed properties [5].…”
Section: /12mentioning
confidence: 99%
“…In recent years, functional fabrics attracted the attention of many researchers. By choosing an appropriate method of fabric modification, it is possible to give them different properties such as waterproofness, 1 incombustibility, 2 ability to self-clean, 3 resistance to UV radiation 4 and antibacterial function. 5 One of the modifications of textiles most often applied is giving them antibacterial properties.…”
mentioning
confidence: 99%
“…Their study revealed that combination of intermingled warp with flat, intermingled and textured weft provided excellent ultra violet radiation protection at 22.5 g/cm 2 fabric areal density. Whereas, presence of twisted yarn has been reduced the UV protection due to the increased openness of fabric structure [71].…”
Section: Uv Protective Textilesmentioning
confidence: 99%